Asesmen Dan Evaluasi Pada Pembelajaran Anak Usia Dini - Iqbal Affandi, Muhammad (STAI Tebing Tinggi Deli, 2023)
Assessment and evaluation of early childhood learning is important to ensure that the learning approach used is appropriate to the child's needs and development. This article will discuss several assessment and evaluation methods that are relevant in the context of early childhood education. First, formative assessment plays a key role in understanding a child's progress in learning. This approach involves teachers observing children's activities, social interactions, and achievements in various skills. The results of formative assessments can be used to adjust learning strategies in real-time, correct weaknesses and strengthen children's strengths. Second, summative assessments provide a more comprehensive picture of a child's progress over a certain period of time. This may involve the use of standardized tests or portfolios that record the child's achievements in various developmental areas such as cognitive, motor, language, and social. The purpose of this research is to determine the implementation of learning evaluation, to determine the use of learning evaluation results in developing learning programs, and to determine the supporting and inhibiting factors in the use of learning evaluation results in developing learning programs. Thus, assessment and evaluation in early childhood learning must be comprehensive, accommodate the needs of individual children, and provide valuable insights for teachers and other stakeholders in improving learning practices and creating an environment that supports children's optimal development.